Chronic Dialysis Discontinuation: A Systematic Narrative Review of the Literature in the New Millennium. Issue 7 (July 2014) - Piccoli, Giorgina Barbara; Guzzo, Gabriella; Vigotti, Federica Neve; Scognamiglio, Stefania; Consiglio, Valentina; Aroasio, Emiliano; Gonella, Silvana; Castelluccia, Natascia; Mauro, Giuseppe; Colombi, Nicoletta
Introduction and aims: Renal function recovery (RFR), defined as the discontinuation of dialysis after 3 months of replacement therapy, is an uncommon occurrence. At a time when the "too early" start of dialysis is in discussion, a systematic review of the literature for cases in which patients recovered renal function after starting dialysis with chronic indications, including single cases and large series, may lead to attention being focused on this interesting issue. Methods: The search strategy was built in Medline on Pubmed, in EMBASE and in the Cochrane Collaboration (August 2013) combining Mesh, Emtree and free terms: dialysis or hemodialysis, kidney function, renal function and recovery (publication date 2000-2013). The following tasks were performed in duplicate: titles and abstracts were manually screened, the data were extracted: title, author, objective, year, journal, period of study, multi-center, country, type of study. Results: The systematic review retrieved 1 894 titles; 58 full papers were retrieved and the final selection included 24 papers: 11 case series or Registry data (4 from ANZdata) and 13 case reports. In spite of the high heterogeneity of the studies, overall they suggest that RFR occurs in about 1% of patients, without differences between PD and HD. RFR appears to be more frequent in elderly patients with renal vascular disease (up to 10% RFR in cholesterol emboli or scleroderma), but is reported in all types of primary and secondary kidney diseases. Conclusions: RFR is a clinical event that should be looked for, particularly in elderly patients with vascular comorbidity.